Autoimmune glial fibrillary acidic protein astrocytopathy masquerading as tuberculosis of the central nervous system: a case series. (November 2022) - Quek, Amy ML; Tang, David; Chin, Amanda; Ng, Kay WP; Lin, Hazel; Seet, Raymond CS
Highlights: Glial fibrillary acidic protein (GFAP) astrocytopathy may respond to steroids used in antituberculous treatment. Brainstem, cerebellar, movement, and/or spinal cord features are typical. Papillitis in the absence of raised intracranial pressure have been reported. Cerebrospinal fluid GFAP-immunoglobulin G should be tested in patients with aseptic meningoencephalitis. GFAP astrocytopathy responds favorably to immunotherapy. Abstract: We describe the case history of three patients with meningoencephalitis who were initially treated for presumed tuberculous meningoencephalitis before being diagnosed with autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy. We highlight the overlapping clinical features between autoimmune GFAP astrocytopathy and tuberculous meningoencephalitis and the challenges in early diagnosis, as both entities respond to an initial course of steroids accompanying antituberculous medications. Early evaluation of GFAP-immunoglobulin G in the cerebrospinal fluid of patients who present with aseptic meningoencephalitis could reveal autoimmune GFAP astrocytopathy, which responds favorably to immunotherapy.